Proximal Femoral Nail Versus Dynamic Hip Screw in Unstable Proximal Femoral Fracture - Yousaf Gul, Inamullah, Muhammad Asghar Essa, Muhammad Zubair Farooq, Shafaat Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Unstable proximal femoral fracture occurs at the top of femur bone, typically in elderly people or those involved in high-impact accidents. The fracture can occur in different ways, including intertrochanteric, subtrochanteric, or femoral neck fractures. The two most common techniques implied for its repair are Proximal Femoral Nail (PFN) and Dynamic Hip Screw (DHS). Objectives: The research was conducted to evaluate these both techniques and compare their clinical outcome in terms of Harris Hip Score, clinical assessment and clinical complications. Methods: Cross-sectional study was completed in 2020-2022 and comprised 104 patients equally divided into Group A (DHS) and Group B (PFN). Both techniques were comparatively analyzed and the outcomes were evaluated using Harris Hip Score and clinical assessment. Results: Group A and B had mean surgery duration of 76.78+13.40 and 57.09+11.67 minutes, mean intra-operative blood loss of 239+32.98 and 149+17.29 ml, mean weight bearing time was 3.13+0.56 and 2.98+0.39 months, average incision length was 8.78+2.81 and 5.12+1.94 cm, radiological union of the fractured bones took 3.27+0.78 and 3.11+0.82 months, respectively. Harris Hip Scores were recorded on monthly basis and revealed that 1st monthly scores of Group A and B were 71 and 74, 2nd month had 77 and 81, 3rd month had 80 and 84, 4th month had 83 and 88, 5th month had 84 and 89 and 6th month revealed 86 and 90 scores, respectively. Practical implication: The surgeons would prefer PFN technique while surgery of unstable femoral fracture to avoid complications and achieve better results. Conclusion: PFN technique was associated with less blood loss, lower complications and a higher Harris Hip Score. It has marginally superior results to DHS. Thus PFN is a minimally invasive technique that necessitates less tissue dissection, resulting in negligible blood loss. In treating unstable femoral fractures, an analysis of clinical indicators revealed that PFN has superior clinical manifestation than DHS. Keywords: Femoral fractures; Harris Hip Scores; Intramedullary device; Osteoporosis.